Performance of Cu-Al2O3 thin film as thermal interface material in LED package: thermal transient and optical output analysis. Issue 1 (2nd January 2018) - Lim, Wei Qiang; Devarajan, Mutharasu; Subramani, Shanmugan
Abstract : Purpose: This paper aims to study the influence of the Cu-Al2 O3 film-coated Cu substrate as a thermal interface material (TIM) on the thermal and optical behaviour of the light-emitting diode (LED) package and the annealing effect on the thermal and optical properties of the films. Design/methodology/approach: A layer-stacking technique has been used to deposit the Cu-Al2 O3 films by means of magnetron sputtering, and the annealing process was conducted on the synthesized films. Findings: In this paper, it was found that the un-annealed Cu-Al2 O3 –coated Cu substrate exhibited low value of thermal resistance compared to the bare Cu substrate and to the results of previous works. Also the annealing effect does not have a significant impact on the changes of properties of the films. Research limitations/implications: It is deduced that the increase of the Cu layer thickness can further improve the thermal properties of the deposited film, which can reduce the thermal resistance of the package in system-level analysis. Practical implications: The paper suggested that the Cu-Al2 O3 –coated Cu substrate can be used as alternative TIM for the thermal management of the application of LEDs. Originality value: In this paper, the Cu substrate has been used as the substrate for the Cu-Al2 O3 films, as the Cu substrate has higher thermal conductivity compared to the Al substrate as shown in previous work.